Decrease In Productivity Of Distribution Of Donation Funds And Alms At The Al-Ghuroba Foundation Mosque Rawamangun East Jakarta - Abdul Aziz; Mukhaer Pakkanna (Cita konsultindo, 2024)
The corona virus pandemic has had a significant negative impact on economic development in various sectors, including philanthropic activities such as Infak and Sedekah. This study focuses on the Decrease in Productivity of Alms and Alms Distribution at the Al-Ghuroba Rawamangun Foundation Mosque, East Jakarta. The main problems raised are the factors causing the decline in productivity of alms and alms distribution and what should be done to increase the productivity of alms and alms distribution. The method used in this study is field research , namely research used through the results of surveys and observations. By using the Case Study approach , namely focusing on a particular object that is raised as a case to be studied in depth so as to be able to uncover the reality behind the phenomenon. This approach can be used in a complementary manner with a descriptive qualitative approach to provide a more comprehensive understanding of a research problem or phenomenon. The results of this study indicate the importance of conducting training evaluations on programs that have been implemented, maintaining harmony with the congregation and donors, and the need for supervision from Baznas in the productivity of distributing alms and donation funds at the Al-Ghuroba Rawamangun Mosque, East Jakarta.